Comparative Impact of Fog and Rainfall on Vegetation in a Foggy Desert - Qiao, Na; Wang, Honglang; Li, Yue; Wang, Lixin (Geophysical research letters, 2024)
Fog is an important water source that alleviates vegetation water stress, especially for dryland ecosystems. Comprehensive knowledge of fog and rainfall effects can help us better understand dryland vegetation responses to current and future climates. However, the differences between fog and rainfall effects on vegetation are poorly understood. This study compared the effects of fog and rainfall on vegetation greenness changes based on the ground‐level meteorological observations in the Namib Desert and the satellite vegetation index. The vegetation index and its first derivative were utilized to indicate vegetation greenness and its change rate, respectively. Results showed that fog played a more significant role than rainfall in explaining vegetation greenness change rates, while accumulated rainfall was more important than fog in determining vegetation greenness. Soil temperature was an important factor in explaining vegetation greenness changes. These findings offer key insights into how fog and rainfall differentially contribute to vegetation greenness changes. Plain Language Summary Dryland plant significantly impacts the global carbon budget, making up about 40% of global net primary productivity. The importance of fog on dryland productivity is highlighted since plant growth in dry areas is strongly constrained by water resources. This study showed that fog consistently appeared among the top five most critical factors in explaining variations in plant greenness and its change rates for both herbaceous and woody areas. Notably, it was found that plant greenness change rates were more influenced by fog than rainfall, although plant greenness was more sensitive to accumulated rainfall than fog. Soil temperature consistently showed large effects on plant greenness changes, potentially limiting plant growth in the context of future global warming. Key Points The first study to simultaneously quantify the effects of fog and rainfall on vegetation greenness changes in a dryland ecosystem Fog was more important than rainfall in explaining vegetation greenness change rates Soil temperature played an important role in vegetation greenness changes with a negative effect